Exploiting recent trends for the synthesis and surface functionalization of mesoporous silica nanoparticles towards biomedical applications - Siddiqui, Bazla; Rehman, Asim.ur; Haq, Ihsan-ul; Al-Dossary, Amal A.; Elaissari, Abdelhamid; Ahmed, Naveed (International journal of pharmaceutics: X, 2022)
Rapid progress in developing multifunctional nanocarriers for drug delivery has been observed in recent years. Inorganic mesoporous silica nanocarriers (MSNs), emerged as an ideal candidate for gene/drug delivery with distinctive morphological features. These ordered carriers of porous nature have gained unique attention due to their distinctive features. Moreover, transformation can be made to these nanocarriers in terms of pores size, pores volume, and particle size by altering specific parameters during synthesis. These ordered porous materials have earned special attention as a drug carrier for treating multiple diseases. Herein, we highlight the strategies employed in synthesizing and functionalizing these versatile nanocarriers. In addition, the various factors that influence their sizes and morphological features were also discussed. The article also summarizes the recent advancements and strategies for drug and gene delivery by rendering smarter MSNs by incorporating functional groups on their surfaces. Averting off-target effects through various capping strategies is a massive milestone for the induction of stimuli-responsive nanocarriers that brings out a great revolution in the biomedical field. [Display omitted] •MSNs serve as an ideal candidate for gene/drug delivery with unique and excellent attributes.•MSNs surface can be functionalized using specific materials to impart unique structural features.•Functionalization of MSNs with stimuli-responsive molecules can act as gatekeepers by responding to the desired stimulus after uncapping.•These capping agents act as vital targeting agents in developing MSNs being employed in various biomedical applications.